Phân tích tác động của giá vàng thế giới đến giá vàng trong nước: Tiếp cận kiểm định Granger phổ - Hoàng Thị Diễm , Hương; Tran Thi Tuan, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This paper employs data from February 2012 to September 2025 to test the spectral Granger causality effect of world gold prices on domestic gold prices. The frequency-domain Granger causality results indicate that prior to the COVID-19 period, world gold prices exerted a strong causality on domestic gold prices across all frequencies, including short-, medium-, and long-term horizons. This finding reflects the close integration between international and domestic gold markets during the relatively stable pre-COVID-19 period. However, in the post-COVID-19 period, no statistically significant Granger causality is detected at any frequency, suggesting that the impact of global gold prices on domestic gold prices has weakened or vanished. This change implies that the COVID-19 shock created a structural break, leading domestic gold prices to no longer respond consistently to fluctuations in world gold prices. For investors, this means that forecasting domestic gold prices based solely on world gold price movements becomes less reliable. Trading strategies relying on international signals should therefore be adjusted or supplemented with domestic factors.